2021
DOI: 10.1007/s00018-021-03967-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the hERG potassium channel by phenanthrene: a polycyclic aromatic hydrocarbon pollutant

Abstract: The lipophilic polycyclic aromatic hydrocarbon (PAH) phenanthrene is relatively abundant in polluted air and water and can access and accumulate in human tissue. Phenanthrene has been reported to interact with cardiac ion channels in several fish species. This study was undertaken to investigate the ability of phenanthrene to interact with hERG (human Ether-à-go-go-Related Gene) encoded Kv11.1 K+ channels, which play a central role in human ventricular repolarization. Pharmacological inhibition of hERG can be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 84 publications
(165 reference statements)
0
14
0
1
Order By: Relevance
“…For instance, substitutions of Y652 or F656 with alanine, which have been known to be crucial residues for the block, abolished the facilitation by nifekalant. Y652 is also crucial for the facilitation of phenanthrene [47]. These findings suggest that facilitation, similar to the block, occurs through interactions within residues that form the central cavity of the hERG pore.…”
Section: Structural Basis Of Herg Facilitationmentioning
confidence: 80%
See 2 more Smart Citations
“…For instance, substitutions of Y652 or F656 with alanine, which have been known to be crucial residues for the block, abolished the facilitation by nifekalant. Y652 is also crucial for the facilitation of phenanthrene [47]. These findings suggest that facilitation, similar to the block, occurs through interactions within residues that form the central cavity of the hERG pore.…”
Section: Structural Basis Of Herg Facilitationmentioning
confidence: 80%
“…Some drugs, known as blockers, reduce both the IV and GV relationships. Additionally, some hERG blockers not only reduce the IV and GV relationships but also shift them to the left, as shown in Figure 1 [36][37][38]43,[45][46][47]. This leftward shift in the GV relationship is referred to as the "facilitation" of voltage-dependent activation by the drug.…”
Section: Facilitation Of Herg Activation By Its Blockermentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that crude oil, or phenanthrene alone, can rapidly impair the function of isolated fish cardiomyocytes by disrupting ion flux. , Follow-up in vitro mutagenesis experiments demonstrated that this is likely due to specific interactions with the cardiac Ether-a-go-go-Related Gene (ERG) encoded K + channels . However, early life-stage exposure to phenanthrene or crude oil impacts numerous organs in addition to the heart.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Follow-up in vitro mutagenesis experiments demonstrated that this is likely due to specific interactions with the cardiac Ether-a-go-go-Related Gene (ERG) encoded K + channels. 14 However, early life-stage exposure to phenanthrene or crude oil impacts numerous organs in addition to the heart. The enduring question is whether some or all of these outcomes are downstream of specific cardiac defects.…”
Section: Introductionmentioning
confidence: 99%